The Influence of Income and Knowledge on Customer Interest in Investing in Gold at PT. Pegadaian Sidareja - Ma’rifatun Nisa; Hatta Setiabudhi; Mutia Pamikatsih (Komunitas Dosen Indonesia, 2025)
This research aims to analysed the influence of income and knowledge on customers interest in investing in gold at PT Pegadaian Sidareja. Gold investment is a popular choice among people as a means of protecting asset values from inflation. However, customers interest in investing is not only influenced by economic factors, but also the knowledge that customers have regarding the benefits and risks of investing in gold. The method used in this research is quantitative with a survey approach. Data was collected through a questionnaire distributed to 84 customers of PT Pegadaian Sidareja. Data analysis was carried out using multiple linear regression to test the influence of income and knowledge variables on investment interest. The research results show that income has a negative effect on customers interest in investing in gold. Meanwhile, knowledge about gold investment has a positive and significant effect on customer interest. Thus, both income and knowledge are important factors that influence customers decisions to invest in gold at PT Pegadaian Sidareja. It is hoped that this research will provide benefits for PT Pegadaian in improving its marketing strategy, especially by emphasizing the importance of investment education to customers to increase interest in investing in gold